Increased Viability of Odontoblast-Like Cells Subjected to Low-Level Laser Irradiation - Oliveira, C. F. [UNESP]; Basso, F. G.; Lins, E. C.; Kurachi, C.; Hebling, Josimeri [UNESP]; Bagnato, V. S.; de Souza Costa, C. A. [UNESP] (Maik Nauka/interperiodica/springer, 2010)
Studies have shown that the increase of cell metabolism depends on the low level laser therapy (LLLT) parameters used to irradiate the cells. However, the optimal laser dose to up-regulate pulp cell activity remains unknown. Consequently, the aim of this study was to evaluate the metabolic response of odontoblast-like cells (MDPC-23) exposed to different LLLT doses. Cells at 20000 cells/cm(2) were seeded in 24-well plates using plain culture medium (DMEM) and were incubated in a humidified incubator with 5% CO2 at 37 degrees C. After 24 h, the culture medium was replaced by fresh DMEM supplemented with 5% (stress by nutritional deficit) or 10% fetal bovine serum (FBS). The cells were exposed to different laser doses from a near infrared diode laser prototype designed to provide a uniform irradiation of the wells. The experimental groups were: G1: 1.5 J/cm(2) + 5% FBS; G2: 1.5 J/cm(2) + 10% FBS; G3: 5 J/cm(2) + 5% FBS; G4: 5 J/cm(2) + 10% FBS; G5: 19 J/cm(2) + 5% FBS; G6: 19 J/cm(2) + 10% FBS. LLLT was performed in 3 consecutive irradiation cycles with a 24-hour interval. Non-irradiated cells cultured in DMEM supplemented with either 5 or 10% FBS served as control groups. The analysis of the metabolic response was performed by the MTT assay 3 h after the last irradiation. G1 presented an increase in SDH enzyme activity and differed significantly (Mann-Whitney test, p < 0.05) from the other groups. Analysis by scanning electron microscopy showed normal cell morphology in all groups. Under the tested conditions, LLLT stimulated the metabolic activity of MDPC-23 cultured in DMEM supplemented with 5% FBS and exposed to a laser dose of 1.5 J/cm(2). These findings are relevant for further studies on the action of near infrared lasers on cells with odontoblast phenotype.